Mechanical Multiscale Lithium-Ion Battery Modeling for Optimized Battery Pack Design - Davide Clerici; Francesca Pistorio; Salvatore Scalzo; Salvatore Martelli; Francesco Mocera; Aurelio Somà (Engineering Proceedings, 2025)
In the automotive and working vehicle industry, lithium-ion batteries are a strategic component affecting the design, cost, and performance of vehicles. The electrochemical processes which allow the battery to deliver or store electrical energy involve the interaction of lithium ions with the electrode microstructure, causing the mechanical deformation of the electrode. The deformation of the electrode microstructure has two effects: mechanical degradation and the resulting overall performance decay of the battery, and macroscopic battery deformation. In this work, macroscopic battery deformation originating at the atomic scale is investigated with a multi-physics homogenized model in two steps: first, the composite electrode is modeled with a representative volume element; secondly, the battery is modeled by homogenizing the contribution of the hundreds of composite electrode layers. Then, the impact of the deformation of the single battery on the whole battery module is numerically investigated. The deformation of the single battery computed with the model is validated with experimental measurements quantifying the macroscopic battery deformation during operation. Then, different design solutions for the battery module are investigated to optimize its energetic and volumetric efficiency while maintaining safe levels of battery module deformation.